Implementasi Pariwisata Berkelanjutan di Eduwisata Enggang Gading - Khoirul Fajri; Taufiq Hidayat; Nelissa Lanjau (Tourism Scientific Journal, 2020)
As a new development paradigm, sustainable tourism is believed to be able to provide a multiplier effect or multiple impacts. The implementation of sustainable tourism is believed to be able to bring progress to Indonesian tourism. This encourages the adoption of sustainable tourism widely, even in areas with low tourism intensity. The research which was held at Enggang Gading Samarinda East Kalimantn, Tourism Center aims to see the implementation of sustainable tourism in the environmental, socio-cultural, and economic fields. The qualitative approach used in this research is the percentage descriptive analysis technique, where the data collection process is carried out through open and in-depth interviews, participatory observation, and documentation study. The results showed that Enggang Gading tourism had implemented activities guided by the principles of sustainable tourism, especially in the application of 3 (three) aspects, namely; physical environmental aspects, socio-cultural aspects, and economic aspects. From the results of an assessment of the results of the informants' answers in each aspect, it shows that the implementation of sustainable tourism on average reaches a score of 67% which means it is in the sufficient category. However, the stakeholders in the Enggang Gading Tourism Edu tour need to increase efforts to implement the environmental, socio-cultural, and economic aspects that are its components so that the percentage of sustainable tourism achievement in the Enggang Gading Edu tour can increase in the future.